Seebeck coefficient of Cu2ZnSnS4 film synthesized by sol-gel process. (2018) - Khottummee, N.; Sumphao, T.; Samapisut, S.; Seetawan, T.
Abstract: This work, we reported on the effect of annealed to characterized and Seebeck coefficient of Copper-Zinc-Tin-Sulfide (Cu2 ZnSnS4 ; CZTS). The CZTS film was deposited on glass slide by dip-coating technique. The precursor solution was prepared by dissolved Copper chloride, Zinc chloride, Tin chloride, and Thiourea in 2-methoxyethanol and drop mono-ethanolamine as stabilizer. The CZTS was dried at 473 K and annealed at 573 K, and 673 K. The formation of crystal structures showed kesterite tetragonal structure in (112), (220), (312), (200), and (322) plans, and corresponding to PDF card number 00-026-0575. It was found that, the crystallite size and thickness are decreased, while lattice strain and Seebeck coefficients were increased with increasing annealed temperature, respectively. The Seebeck coefficient can optimized by observation temperature range of 573 and 673 K.